Consolidation of nanocrystalline hydroxyapatite powder - Ramesh, S.; Tan, C.Y.; Sopyan, I.; Abd Shukor, Mohd Hamdi; Teng, W.D. (2007)
The effect of sintering temperature on the sinterability of synthesized nanocrystalline hydroxyapatite (HA) was investigated. The starting powder was synthesized via a novel wet chemical route. HA green compacts were prepared and sintered in atmospheric condition at various temperatures ranging from 900-1300 degrees C. The results revealed that the thermal stability of HA phase was not disrupted throughout the sintering regime employed. In general, the results showed that above 98 of theoretical density coupled with hardness of 7.21 GPa, fracture toughness of 1.17 MPa m(1/2) and Young's modulus of above 110 GPa were obtained for HA sintered at temperature as low as 1050 degrees C. Although the Young's modulus increased with increasing bulk density, the hardness and fracture toughness of the sintered material started to decline when the temperature was increased beyond 1000-1050 degrees C despite exhibiting high densities > 98 of theoretical value. The occurrence of this phenomenon is believed to be associated with a thermal-activated grain growth process. (c) 2006 NIMS and Elsevier Ltd. All rights reserved.